Anderson & Krahthwohl Cognitive Applications in Teaching and Learning Pantun in Elementary Schools - Mohamed, Ros Anita Kartini; Ali, Abdul Halim; Nasir, Muhammad (Journal of Humanities and Social Sciences (JHASS), 2021)
Taksonomi adalah klasifikasi benda mengikut ciri-ciri tertentu. Taksonomi dalam bidang pendidikan digunakan untuk mengklasifikasikan tujuan pendidikan, penyusunan penilaian dan kurikulum. Bloom telah mengkategorikan tiga ranah dalam pembelajaran, yaitu; ranah kognitif, ranah afektif dan ranah psikomotor. Taksonomi Bloom fokus pada terminologi (1) pengetahuan; (2) pemahaman; (3) penerapan; (4) analisis; (5) sintesis; dan (6) evaluasi. Sedangkan terminolginya berubah dengan adanya Taksonomi Revisi pada tahun 2001 oleh Anderson & Krathwohl dengan terminologi (1) mengingat; (2) memahami; (3) mengaplikasikan; (4) menganalisis; (5) menilai; dan (6) mencipta. Terminologi ini berubah dengan mempertimbangkan keperluan holistik agar lebih mudah dalam penerapannya oleh guru di sekolah. Fokus utama makalah ini adalah membahas ranah kognitif Revisi Anderson & Krathwohl 2001 dan penerapannya dalam pengajaran dan pembelajaran pantun di sekolah dasar. Anderson & Krahthwohl Cognitive Applications in Teaching and Learning Pantun in Elementary Schools Abstract: Taxonomy is the classification of things according to certain characteristics. Taxonomy in education is used to classify educational objectives, assessment and curriculum preparation. Bloom has categorized three domains in learning, namely; cognitive domain, affective domain and psychomotor domain. Bloom’s taxonomy focuses on the terminology of (1) knowledge; (2) understanding; (3) application; (4) analysis; (5) synthesis; and (6) evaluation. While the terminology changed with the introduction of the Revised Taxonomy in 2001 by Anderson & Krathwohl with the terminology (1) recalling; (2) understand; (3) apply; (4) analyze; (5) evaluate; and (6) create. This terminology changes by considering the holistic need to make it more relevant in its application by teachers at the school level. The main focus of this paper is a discussion on the cognitive domain of the 2001 Anderson & Krathwohl Revision and its application in the teaching and learning of verse in primary schools. Keywords: Bloom's Taxonomy, Cognitive Area, Poetry, Revised Taxonomy.